THE RELATIONSHIP OF EMESIS GRAVIDARUM WITH THE INCIDENT OF ANEMIA IN THE MOTHER PREGNANT - Permata Sari, Septi Indah; Susilawati, Elly (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2024)
Hyperemesis gravidarum is nausea and vomiting which is categorized as severe if a pregnant woman vomits every time she drinks or eats. Meanwhile, pregnancy anemia is a